Conceptualising community radio: from global histories to the Kenyan example - Korir, Geoffrey Kiplimo (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2020)
This study sets out to gain insight into the way that the establishment of community radio in Kenya is located within the global history of ideas about such radio. The first four chapters in this study provide terms of reference for this examination through a series of literature reviews. It sets out, firstly, to locate the internationally shared conceptualisaiton of community radio within an existing spectrum of approaches to social analysis. It proposes that community radio can be located at the critical, emancipatory end of this spectrum. It then maps out the global circulation of ideas about community radio and proposes that such circulation was informed by the broader history of critical, emancipatory social analysis. The final literature review then deals with community radio in Kenya and examines the way in which the establishment of this sector was shaped by the social and political history of this country. It is argued that the establishment of a community radio sector became possible only when support for emancipatory approaches to media became acceptable in Kenya, in context of the establishment of multiparty democracy. It is proposed, further, that the articulation of a vision for community radio in Kenya depended in part on the existence of international support for such radio and in part on the efforts of local actors in civil society. The empirical component then focuses on the way global ideas about community radio have become realised in Kenya. The study achieves this purpose by drawing on qualitative interviews with individuals from within civil society who have participated in the history of the establishment and growth of community radio in Kenya. These individuals demonstrate consciousness of the internationally shared set of principles that can facilitate a successful establishment of community radio. However, they are also sceptical of the assumption that guidelines for community radio are universally applicable. They point, in particular, to the challenges involved in the realisation of these guidelines in an environment in which economic resources are limited, and which is characterised by extreme social inequality and conflict. The study concludes that it is individuals such as these participants, who are embedded within the local context, who are best placed to articulate locally appropriate alternatives to these guidelines.
Keywords: Community radio; Community radio -- Kenya; Community development -- Kenya; Social change -- Kenya; Radio broadcasting -- Kenya